Changes in neurocognitive functioning during transition to manifest disease: comparison of individuals at risk for schizophrenic and bipolar affective psychoses. Issue 10 (2nd February 2015) - Metzler, S.; Dvorsky, D.; Wyss, C.; Müller, M.; Gerstenberg, M.; Traber-Walker, N.; Walitza, S.; Theodoridou, A.; Rössler, W.; Heekeren, K.
Abstract : Background: Neurocognitive deficits are important aspects of schizophrenic disorder because they have a strong impact on social and vocational outcomes. Previously it was assumed that cognitive abilities progressively deteriorate with illness onset. However, recent research results have contradicted this with observations of continuous or even improved performance in individuals at risk for psychosis or manifest schizophrenia. The objective of our longitudinal study was to examine neurocognitive functioning in help-seeking individuals meeting basic symptoms or ultra-high-risk criteria for schizophrenic psychosis (HRSchiz) or risk criteria for affective psychosis (HRBip). The progression of cognitive functioning in individuals converting to psychosis was compared with that of at-risk individuals who did not convert during the follow-up period. Method: Data were available from 86 study participants who completed neurocognitive and clinical assessments at baseline and, on average, 12.8 (s.d.  = 1.5) months later. Neurocognitive measures were grouped according to their load in factor analysis to five cognitive domains: speed, attention, fluency, learning and memory, and working memory. Results: Neurocognitive functioning in HRSchiz and HRBip individuals generally improved over time. Subjects converting to manifest psychosis displayed a stable neurocognitive profile from baseline to follow-up. Compared with non-converters, they had already demonstrated a significantly lower level of performance during their baseline examinations. Conclusions: Our data provide no evidence for a progressive cognitive decline in individuals at risk of psychosis. In line with the neurodevelopmental model, our findings suggest that cognitive deficits are already present very early, before or during the prodromal stage of the illness.